LEAN MANUFACTURING IMPLEMENTATION FOR NEW PRODUCT DEVELOPMENT EFFECTIVENESS: CASE STUDY ON THE INDUSTRY OF WIRE STEEL AND DERIVATIVES - Muharom Muharom; M. Hasan Abdullah (Journal of Engineering and Management in Industrial System, 2019)
Manufacturing organizations faces many changes along with the occurrence of environmental changes, it comes from internal and external sources. Innovation become one of the keywords to help the organizations be more competitive, such as doing product development. First, digging through from the survey, the customer’s needs as the initial planning phase, concept development, system level design, detail design, test and reparation details among the beginning of production. During the product development process, the Organization has not identified the potential waste in detail yet at each stage of product development. Moreover, the repair process becomes less effective. By using this concept, it will help in potential waste identify. The results showed that the stage of concept development had the highest frequency, for instance the common of lacking information related to the customers need products information which will be developed. Then, frequency is happened on the stage of the testing, and refinement, detail design, system level design and planning. Through the concept of lean VSM can be known by using a value of VA 53%, NVA 29% and 18% Waste, time to market can be shortened 18% or 47 days from early 262 days be 215 days.